(3TQM GdYhGed GdLQLGfjIs - (3GdchQGfj, EHQGgje Hf MSf, J(B1101(3g`s ((3GdehUds)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf MeOG WjHG cKjQG eHGQcG CeG HYO agPg cdeGJ eagheGJ agefGgG ef cdGe GdTGQM deJhf GdfMhs
(3BNQgG (B:s
(3Yf GdLGRe hGdfGUH dCfg EPG THg HGdGSe aGbJVi GdEYdQGH ef GdeTGHgI aEPG de jcf LGReG ajdReg Cf jchf eQahYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 35s
(3eYLe GdeDdajf(B: 1 / 19s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs